Professionals’ perceptions of interprofessional collaboration within condition-based units - Sara M. de Jong-Ultee; Liselot de Waard; Dorine J. van Staalduinen; Machteld J. Mosselman; Dennis van Veghel; Lea M. Dijksman; Paul B. van der Nat (PLoS ONE, 2026)
Introduction Hospitals can form condition-based units (CBUs) to support value-based healthcare (VBHC). Interprofessional collaboration is key to the success of CBUs, but insights into its quality are lacking. We aimed to examine professionals’ perceived quality of interprofessional collaboration in CBUs, and factors influencing it. Methods A single-center mixed-methods study was conducted within four CBUs in a Dutch top-clinical hospital: (1) geriatric trauma, (2) prostate cancer, (3) colon cancer and (4) breast cancer. A relational coordination (RC) survey was used to examine professionals’ perceived collaboration quality, followed by semi-structured interviews to explore influencing factors. Results Varying RC scores were observed between professionals with different professions and disciplines within CBUs (geriatric trauma: 1.9–5.0; prostate cancer: 2.9–4.8; colon cancer: 2.1–4.8; breast cancer: 1.1–4.9), with higher scores among professionals involved in similar parts of related care pathways. Interview findings suggest that this variation is explained by four factors: (1) streamlined communication, (2) active engagement, (3) mutual recognition and (4) workflow efficacy. Conclusion This exploratory study introduces a novel approach to studying professionals’ perceived collaboration quality in CBUs through relational dynamics. The results suggest that traditional hospital structures can hinder interprofessional collaboration in CBUs by limiting physical interactions and shared administrative systems. Future studies with larger samples are needed to confirm these findings, and to provide recommendations for improving interprofessional collaboration in CBUs in order to unlock their potential in improving patient care.